Peranan Purchasing dalam Pengadaan Barang di Departemen Perusahaan PT Indobismar Surabaya - Mochammad Rizky Nur Ardiansyah; Ari Susanto (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to examine the role of purchasing in procurement at PT Indobismar Surabaya and analyze the factors influencing the effectiveness and efficiency of the purchasing function. The research employs a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and document analysis. The findings reveal that purchasing plays a strategic role in procurement planning, supplier evaluation, price negotiation, as well as quality and quantity control of received goods. The implementation of structured procurement procedures and the use of information technology such as e-procurement have enhanced the efficiency and transparency of the procurement process. Purchasing also manages risks associated with supply uncertainty and price fluctuations by diversifying suppliers and building long-term relationships. Furthermore, purchasing supports innovation and product quality improvement through collaboration with production and research & development departments. However, the research identifies challenges such as budget constraints and fluctuations in raw material prices in the global market. Overcoming these challenges requires continuous market analysis and adaptation to changes to ensure smooth procurement processes. This study provides insights into the importance of the purchasing function and offers practical recommendations to enhance purchasing performance at PT Indobismar Surabaya. The research findings are expected to enrich the literature on procurement in the manufacturing industry in Indonesia and provide a basis for further research.